Groundwater Quality in Jingyuan County, a Semi-Humid Area in Northwest China. Issue 2 (2011) - Jianhua, Wu; Peiyue, Li; Hui, Qian
Abstract : Groundwater quality assessment is an essential study which plays an important role in the rational development and utilization of groundwater in any part of the world. In the study, groundwater qualities in Jingyuan County, in Ningxia, China were assessed with entropy weighted water quality index method. In the assessment, 12 hydrochemical parameters including chloride, sulphate, sodium, iron, pH, total dissolved solid (TDS), total hardness (TH), nitrate, ammonia, nitrogen, fluoride, iodine and nitrite were selected. The assessment results show that the concentrations of iodine, TH, iron and TDS are the most influencing parameters affecting the groundwater quality. The assessment results are rational and are in consistency with the results of filed investigation of which both indicates the groundwater in Jingyuan County is fit for drinking.